Status Sosial Ekonomi dan Keragaman Pangan Pada Balita Stunting dan Non-Stunting Usia 24-59 Bulan di Wilayah Kerja Puskesmas Wilangan Kabupaten Nganjuk - Atin Nurmayasanti; Trias Mahmudiono (Amerta Nutrition, 2019)
Background: Stunting is a chronic nutritional problem caused by poor nutritional intake and infectious diseases. Other causes are maternal socio-economic and nutritional conditions during pregnancy. Nutritional quality in food is influenced by the diversity of types of food consumed. Food diversity can be determined by prosperity, children's age, and mother's education. Economic conditions have a risk of stunting because they can describe the family's ability to fulfill nutritious food intake.Objective: This study aimed to analyze the relationship between socio-economic and food diversity with the incidence of stunting in children aged 24-59 months.Method: This study was an observational study with case control research design. The population in this study were children aged 24-59 months who were enrolled in Posyandu in the Puskesmas Wilangan working area. The sample size taken by each 28 toddlers was selected through simple random sampling. The food diversity score is obtained from the Individual Dietary Diversity Score (IDDS) score. Descriptive data analysis to describe toddler age, gender, mother's education, and mother's work. While inferential analysis used the chi-square test to determine the relationship between food diversity and income level with the incidence of stunting.Results:The results showed that family income was related to the incidence of stunting in infants (p = 0.048). Low family income is at risk of getting stunting. Scores of food diversity for stunting and non-stunting children are still low. The chi-square results show that there is no relationship between food diversity and the incidence of stunting (p = 1.000) and not a risk factor for stunting toddlers (OR = 1.000).Conclusion: Family income has a significant relationship with the incidence of stunting. Food diversity is not related to stunting.ABSTRAKLatar Belakang: Stunting adalah masalah gizi kronis yang disebabkan oleh asupan gizi yang kurang dan penyakit infeksi. Penyebab lain adalah kondisi sosial ekonomi dan gizi ibu saat hamil. Kualitas gizi pada makanan dipengaruhi oleh keragaman jenis pangan yang dikonsumsi. Keragaman pangan dapat ditentukan oleh kesejahteraan, usia anak, dan pendidikan ibu. Kondisi ekonomi memiliki risiko terjadinya stunting karena dapat menggambarkan kemampuan keluarga dalam memenuhi asupan makanan yang bergizi.Tujuan: Penelitian ini bertujuan untuk menganalisis hubungan antara sosial ekonomi dan keragaman pangan dengan kejadian stunting pada balita usia 24-59 bulan.Metode: Penelitian ini adalah jenis penelitian observasional dengan desain penelitian case control.  Populasi pada penelitian ini anak balita usia 24-59 bulan yang terdaftar dalam Posyandu wilayah kerja Puskesmas Wilangan. Besar sampel yang diambil masing-masing 28 balita yang dipilih melalui simple random sampling. Skor keragaman pangan diperoleh dari skor Individual Dietary Diversity Score (IDDS). Analisis data secara deskriptif untuk menggambarkan usia balita, jenis kelamin, pendidikan ibu, dan pekerjaan ibu. Sedangkan analisis inferensial menggunakan uji chi-square untuk mengetahui hubungan keragaman pangan dan tingkat pendapatan dengan kejadian stunting. Hasil: Hasil penelitian menunjukkan pendapatan keluarga berhubungan dengan kejadian stunting pada balita (p=0,048). Pendapatan keluarga yang rendah berisiko terkena stunting. Skor keragaman pangan pangan balita stunting maupun non-stunting sama-sama masih rendah. Hasil chi-square menunjukkan bahwa tidak ada hubungan antara keragaman pangan dengan kejadian stunting (p=1,000) dan bukanlah faktor risiko balita stunting (OR = 1,000).Kesimpulan: Pendapatan keluarga memiliki hubungan yang signifikan dengan kejadian stunting. Keragaman pangan tidak berhubungan dengan stunting.